Anjela Duval : un modèle de consécration littéraire ? - Mannaig Thomas (La Bretagne Linguistique)
The processes of recognition from which writers benefit can be very varied, both in terms of their modalities, temporalities and spatial extensions, but also in the way they can end up being naturalised. This article looks at the various stages in the consecration process that made the Breton-language poet Anjela Duval a regional figure recognised well beyond her initial literary sphere. Anjela Duval has benefited, and continues to benefit, from a wide range of forms of recognition, some of them literary (the publication of her complete works, for example), but also from a much wider visibility (odonymy, statues bearing her effigy, names given to various institutions...).